Capturing the Cloud: Towards SharePoint Transfer at UK Parliament - Nicole Hartland; Emily Chen; Rosemary Reynolds (International Journal of Digital Curation)
Since 2020, UK Parliament has moved towards cloud-based ways of working and collaboration, with colleagues across both Houses increasingly storing and sharing most of their information in Microsoft SharePoint. In response to this shift, the Parliamentary Archives sought to establish an end-to-end process to transfer information of archival value out of SharePoint and into the Digital Repository. Three challenges, unique to the cloud-based and collaborative nature of this environment, arose: defining the authoritative version, extracting files from the cloud with properties and metadata intact, and validating and authenticating files in the cloud. This brief report outlines the Parliamentary Archives efforts to explore and test the transfer and authentication of archival data from the cloud and into their digital repository with a focus on building trust and transparency.